Bahasa Indonesia Bahasa Indonesia - Arinda Jayanti Putri; Tedjo Sukmono; Ervan Johan Wicaksana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine The Effect of Learning Models Problem Based Learning (PBL) Based on STEM Approach to E-Phase Critical Thinking Ability in Biology Learning. Research using type experimental research pretest-posttest control grup design with technique random sampling. So that phase E-5 was chosen as the experimental class, phase E-7 as the control class, with a total of 36 students in each class. The data analyzed were the results of the initial test and the final test on questions of critical thinking ability, with data analysis using the SPSS, testing the hypothesis using the ANOVA test. The results of the ANOVA test analysis show that the application of the Problem Based Learning (PBL) model based on the STEM approach has a significant effect on students' critical thinking skills at SMA Negeri 4 Jambi City. The data collection method used is a critical thinking ability test, response questionnaire, activity observation.